The Gambia - Fiscal Developments and the Agriculture Sector : Public Expenditure Review Update - World Bank (Washington, DC, 2012)
The objectives of this Public Expenditure Review (PER) update are to analyze public expenditures of the overall budget and the agriculture sector in greater detail. The authorities prepared sectoral PER of the agriculture and natural resources sectors in 2001. The second chapter of this PER update is a partial update of the 2001 sectoral PER. It focuses only on the agriculture sector and excludes the natural resource sectors, and it does not analyze the sector strategy or the latest sector developments. The macroeconomic environment continued on its stable path in recent years. The authorities have gradually tightened fiscal and monetary policies since the economic downturn in 2002, resulting in a resumption of growth, lowering of inflation, and stabilization of the exchange rate. The authorities are currently developing the agriculture sector strategy. This should be based on a comprehensive analysis of the latest sector developments, including identification of key sector constraints.